How to improve your ART success rates an evidence-based review of adjuncts to IVF - Kovacs, Gabor 1947 April 6- (Cambridge University Press, 2011)
IVF is now established worldwide as a clinical service. Units are striving to improve their success rates, and many treatments are being advocated as 'yet another breakthrough'. The purpose of this book is to help clinicians to evaluate each of these new treatments. Each chapter is written by a recognized international expert in the field and the chapters are short and succinct, summarizing the latest evidence-based information for each topic and treatment. Sections cover patient selection and preparation, the role of AIH before IVF, stimulation, monitoring, laboratory techniques, embryo transfer, ancillary treatments and assessment of results. How to Improve your ART Success Rates: An Evidence-Based Review of Adjuncts to IVF is essential reading for all clinicians working with infertility and assisted reproduction, and is also a valuable addition to any medical library